2019
DOI: 10.1039/c9cc04294f
|View full text |Cite
|
Sign up to set email alerts
|

Diborane heterolysis and P(v) reduction by Ph3PO coordination to magnesium

Abstract: Inner sphere attack of Ph3PO provides a terminal magnesium boryl, which is a potent reagent for the deoxygenation of P(v).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…In a manner analogous to the generation of II and III, reaction of the -diketiminato organomagnesium derivative, [(BDI)Mgn-Bu] (IV: BDI = HC{(Me)CNDipp} 2 ; Dipp = 2,6-di-iso-propylphenyl), with commercially available bis(pinacolato)diboron (B 2 pin 2 ) results in the quaternisation of the diboron compound to yield a B(sp 2 )-B(sp 3 ) diboranate species, V. 53,54 Subsequent addition of strongly coordinating bases, such as 4-dimethylaminopyridine (DMAP), promotes the rupture of the B-B bond to generate magnesium boryls such as VI, through the elimination of n-BuBpin (Scheme 1). [53][54][55] Although species such as VI are readily envisaged as sources of the {Bpin}  anion, compound V has, in its own right, been shown to act as a nucleophilic boron surrogate and as a conveniently generated reagent for nucleophilic B-C and B-B bond formation when reacted with suitable C-or B-centred electrophiles. 53,[56][57][58][59] Reactions of V with triphenylphosphine oxide and a variety of organic imines have implied that the mode of B-B heterolysis can encompass significant mechanistic diversity invoking either an 'inner'…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a manner analogous to the generation of II and III, reaction of the -diketiminato organomagnesium derivative, [(BDI)Mgn-Bu] (IV: BDI = HC{(Me)CNDipp} 2 ; Dipp = 2,6-di-iso-propylphenyl), with commercially available bis(pinacolato)diboron (B 2 pin 2 ) results in the quaternisation of the diboron compound to yield a B(sp 2 )-B(sp 3 ) diboranate species, V. 53,54 Subsequent addition of strongly coordinating bases, such as 4-dimethylaminopyridine (DMAP), promotes the rupture of the B-B bond to generate magnesium boryls such as VI, through the elimination of n-BuBpin (Scheme 1). [53][54][55] Although species such as VI are readily envisaged as sources of the {Bpin}  anion, compound V has, in its own right, been shown to act as a nucleophilic boron surrogate and as a conveniently generated reagent for nucleophilic B-C and B-B bond formation when reacted with suitable C-or B-centred electrophiles. 53,[56][57][58][59] Reactions of V with triphenylphosphine oxide and a variety of organic imines have implied that the mode of B-B heterolysis can encompass significant mechanistic diversity invoking either an 'inner'…”
Section: Introductionmentioning
confidence: 99%
“…or 'outer sphere' approach of the Lewis basic reagent. 55,56 Addition of triphenylphosphine oxide to compound V provided a Ph 3 P=O-coordinated magnesium boryl species, VII, which is otherwise analogous to compound VI (Scheme 2(a)). Although computational (DFT) assessment of this reaction implied that the B-B' cleavage was induced by inner sphere coordination of the P=O bond to magnesium, 55 reactions of V with more sterically encumbered imine reagents provided the N-B bonded organomagnesium compounds as the initially formed kinetic products (Scheme 2(b)).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current work emerged from our studies of magnesium-centered boryl nucleophiles and, [13][14][15] specifically, their use in the construction of B À B' bonds (Scheme 1). [16,17] We have previously reported that treatment of [(BDI)MgBu] (BDI = HC{C(Me)N-2,6-i-Pr 2 C 6 H 3 } 2 ] with bis(pinacolato)diboron (B 2 pin 2 ) provides the diboranate derivative, compound 3 (Scheme 1).…”
mentioning
confidence: 99%